Pengetahuan dan Persepsi Remaja Tentang Rokok Elektrik - Wahyuni, Fitri; Choiruna, Hasby Pri; Diani, Noor (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2021)
The use of electric cigarettes in teenagers is increasing with the circulation of informationthat electric cigarettes can be used as a tool to stop the use of conventional cigarettes. Thepurpose of this research was to determine the knowledge and perceptions of teenagers aboute-cigarettes. This research is a descriptive research with 120 respondents.Respondents weredivided into two schools, A (n=96) dan B (n=24), taken from each class which class X toclass XII. The data was taken in January 2019 using the questionnaire method. As many as61 people (50.7%) respondents had less knowledge (p-value ≤6) and as many as 64 people(53.4%) respondents had negative perceptions (p-value ≤2). The role of the government,health workers, mass media and teachers is also needed for education and regulation tochange teenagers knowledge and perceptions of e-cigarettes and to reduce new users of ecigarettes.